Evaluasi Program Tahfidz Qur’an Dengan Model Goal Free Evaluation - Reski Reski (JURNAL MAPPESONA, 2024)
The current era of globalization is very sophisticated, both in terms of technology and media. The current era is prone to negative influences, so the next generation needs a strong fortress. The teaching of the Qur'an to children is the first foundation of Islamic education which must be taught when children are at an early age. SMA Negeri 14 Bone as one of the secondary schools in this area has organized a Qur'an tahfidz program so that it can improve the quality of its students and one way that can be done is to develop children's character including religious character. The name guarantees the success of the Qur'anic tahfidz process, the evaluation of the planning and implementation of the Qur'anic tahfidz program is very important. This study aims to evaluate the Qur'an tahfidz program at SMA Negeri 14 Bone. The research method used is qualitative method. The results showed that the evaluation of the Qur'an tahfidz program at SMA Negeri 14 Bone went well as expected.